Virtual environments and contemporary artistic performances in relation to some American shamanistic healing ceremonies (an interactive creativity approach) (2011)
The article points out the existent interaction among contemporary performances, virtual environments and some shamanistic healing ceremonies in America. It presents several classifications of performance art in relation to anthropology, definition camps and other new perspectives weighted against different artistic visions and theoretical frames, emphasizing on the degree of appropriation, usage and manipulation of traditional healing practices associated amid ritual observance, with the possible interrelations and interactivities of art signage, design and movement notions mediated by both the public and technology, in order to construct an idea of co-authorship of art works according to simulation strategies. It exposes the process of configuration, materialization and socialization of a particular creation system developed by the author, as well as its basic formulation pillars brought from interactivity media management, sign/art body experience and the critical reflection about the vision/tradition relationship on contemporary society towards healing shamanistic ceremonies, relational aesthetic experiences and culture transmission phenomena.